Childhood Cancer in Zimbabwe: A Review of KidzCan's Database - Laura P.V. Sibanda; Anel Van Zyl; Tonya M. Esterhuizen; Daniel Mackenzie; Loyce Hlatywayo; Patience Kuona; Mariana Kruger (JCO Global Oncology)
PURPOSEThis study estimated the childhood cancer incidence in Zimbabwe between January 2015 and December 2021.PATIENTS AND METHODSData collected from Zimbabwe's KidzCan database and patient files included demographic data (sex, date of birth, age at diagnosis, and geographic home region), cancer diagnosis, and orphanhood. The age-specific incidence rate per million population at risk for children age 0-14 and 0-19 years was calculated using the United Nations Statistics Division population estimates for Zimbabwe in 2021, with estimates for 0-4 years, 5-9 years, 10-14 years, and 15-19 years age groups.RESULTSA total of 1,090 cases were identified, of which 1,024 were analyzed; 66 were excluded because of missing data. The median age was 4 years (range, 0-17 years), and the male-to-female ratio was 1.2:1. More than half (54.2%; 555) were between age 0 and 4 years. Most patients had solid tumors (70.4%). The study's age-specific rates were 161.76/million population at risk for the 0-14 years age group compared with the reported International Incidence of Childhood Cancer-3 data for Zimbabwe (1993-2013) of 126.3/million, whereas it was 132.75/million population at risk for the 0-19 years age group. The most common cancers were nephroblastoma (22.1%), acute leukemia (21%), and retinoblastoma (15%).CONCLUSIONThis study provides crucial incidence data regarding childhood cancer in Zimbabwe, which may assist in policy planning to achieve the 2030 WHO goal of a 60% cure rate. These results indicate the crucial role of civil society organizations such as KidzCan in assisting the Zimbabwe government in managing childhood cancer.